Aflatoxin Contamination in Hazelnut Oil Obtained from Hazelnuts Containing High Levels of Aflatoxin - Bünyamin Şengül; Elif Apaydın; Enis Taşçı; Rıdvan İlgün; Ümit Şengül (Journal of Agricultural Sciences)
In this study, the issue of whether the aflatoxin in high contaminated hazelnut has been passed to the hazelnut oil during production or not has been investigated. The oil and oil cake of the hazelnut samples that contained aflatoxin at a high level were obtained for the study. The aflatoxin concentrations in hazelnut, hazelnut oil and oil cake were measured, and how much of the aflatoxin in the hazelnut was passed into the oil and oil cake has been determined. Aflatoxin analysis was performed using AOAC (Association of Official Analytical Chemists Method): 991.31 method, which is one of the validated method used in aflatoxin analysis in hazelnuts. The highest aflatoxin concentration in hazelnut oil has been determined as AFB1: 0.93, AFG1: 0.52, AFB2: 0.47 and AFG2: 0.21 μg kg-1. At the end of the study, it was determined that although the hazelnuts of which the hazelnut oil was obtained contained aflatoxin at a very high level, it was passed to the oil at very low levels below the maximum limits defined by the European Union, and almost all of it remained in the oil cake. Aflatoxin in hazelnut is passed to hazelnut oil at very low amount.